Serum CRP level in day of ovum pickup and embryo transfer as a predictor for success in patients undergoing IVF/ ICSI - Mohamed, Mofeed F.; Zakria, Abd El-Moneim M.; El-Sayed, Walid M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: This study was performed to determine the level of serum C-reactive protein (CRP) in day of ovum pickup and embryo transfer as a predictor for success in patients undergoing In-Vitro Fertilization (IVF) and Intracytoplasmic Sperm injection (ICSI). Methods: This study was a cross sectional study (prospective) that was conducted in assisted reproduction unit in Al-Azhar University Hospital on 50 infertile patients who were candidate for IVF/ICSI, using standard long protocol, blood was drawn two times during cycle, in the day of ovum pick up and the day of embryo transfer. Results: In (70.6 %) the serum of CRP level was higher in day of embryo transfer than day of ovum pick up. The ratio of CRP level in the day of embryo transfer to the day of ovum pick up was heigher (1.54) in patients who became pregnant after ICSI, patients with less than this ratio have not been pregnant. Conclusions: Controlled ovarian hyper stimulation and puncture of ovaries can potentiate systemic stimulation so increasing serum CRP level in day of embryo transfer rather than day of ovum pick up can predict success in patients undergoing IVF/ICSI.